PELATIHAN MENINGKATKAN PRODUKTIVITAS DAN KREATIVITAS PADA KARYAWAN TRANS RETAIL - Liem Bambang Sugiyanto; Fahrul Riza; Michael Christianto (Jurnal Abdimas Bina Bangsa, 2022)
The purpose of this activity is to establish synergy between universities and corporations in sharing knowledge to produce creative and productive human resources. The method of community service activities is carried out through webinars. The activity was attended by 173 employees of various levels from the operational division of Trans Retail Indonesia. The results of the activity evaluation showed that participants felt they had benefited from this activity, such as adding knowledge after being busy with routines every day, feeling that they had new energy to continue their education. The four elements of the assessment which consist of educative, objective, accountable and transparent get the above responses well